Legal Reconstruction of the Police Code of Ethics in Strengthening Sanctions against Members Involved in Narcotics Abuse - Andin Wisnu Sudibyo; Faisal Santiago (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Artificial intelligence (AI), particularly deepfake technology, has greatly influenced society by enabling the creation of fake pornographic content. This phenomenon threatens privacy, reputation, and mental well-being. In Indonesia, laws addressing pornography and electronic crimes exist but are inadequate to manage AI-driven crimes such as deepfake pornography. The absence of specific legal frameworks poses challenges to effectively tackling these issues. Purpose. This study aims to examine the inadequacies of current Indonesian regulations in dealing with deepfake pornography and propose a legal reconstruction of the Police Code of Ethics to strengthen sanctions against perpetrators. The research also explores ways to balance strict legal measures with the encouragement of beneficial technological advancements. Method. A qualitative research method was employed, involving a review of legal documents, regulations, and case studies related to deepfake pornography and AI-related crimes. Comparative analysis with other countries’ laws was conducted to identify best practices. Results. The findings reveal gaps in the Indonesian legal framework for addressing AI-related crimes. Recommendations include the formulation of new regulations that specifically address deepfake technology, stronger sanctions, and the integration of ethical AI use in law enforcement practices. Conclusion. Responsive legal frameworks that regulate AI use and strengthen sanctions are essential for protecting individuals and enhancing law enforcement. This ensures that technological innovations serve societal benefits without causing harm.